Low data rate visible light communication system - Farias, Gonçalo Nuno Brás (2015)
Recent advances in light emission diodes (LED) technology led them to an important place on lighting systems. This conquer allied to its switching speed permitted the development of new visible light communication systems (VLC), these are included in unguided optical communications. In the past, unguided optical communications were restricted to infrared spectrum due to LEDs ine ciency, but nowadays this is changing. Visible light communication systems can o er viable or complementary alternatives to the existing communication systems, due to its easy integration in certain environments. One possible integration environment are the mobile communications, and that fact is in the origin of this work. Old mobile phones had interfaces that allowed optical communication, for example IrDA but with the advances of technology these become obsolete and were eliminated. Due to that, modern smartphones do not o er any kind of interface for optical communications. However most of them have one camera that uses a ash device based on high intensity LEDs. Controlling with some precision one smartphone ash allows the implementation of one low data rate VLC systems which can be used for smart tagging, remote control of electronic devices or to control access to buildings. The main goal of this project is study the viability of the use of one smartphone as emitter in a VLC system.